Diverting colostomy in a child with Fournier's gangrene, a case report - Maidah A. Al-Garni; Rahaf H. Baharoon; Nasir M. Bustangi (Elsevier, 2021)
Fournier's gangrene (FG) is a necrotizing infection of the perineum and genitalia that is considered uncommon in the pediatric age group, and it necessitates aggressive treatment. The use of diverting colostomy in the management is still controversial. In this paper, we present a case of a 7-month-old male infant with eczema who presented with a history of fever for 3 days and peri-scrotal swelling. A diagnosis of Fournier's gangrene was made based on clinical examination, radiological and intraoperative findings. Our patient went for surgery and a diverting colostomy was decided intra-operatively to decrease fecal contamination and enhance fast recovery. The patient recovered very well in a short period without the need of total parenteral nutrition (TPN) or complications related to the surgery and was discharged home in a good health. We suggest that further studies to explore the role and benefits of diverting colostomy in the management of FG in pediatric population should be conducted.